The looming tide of nontuberculous mycobacterial infections in Portugal and Brazil - Costa, Daniela Nunes (2016)
Nontuberculous mycobacteria (NTM) are widely disseminated in the environment and an emerging cause of infectious diseases worldwide. Their remarkable natural resistance to disinfectants and antibiotics and an ability to survive under low-nutrient conditions allows NTM to colonize and persist in man-made environments such as household and hospital water distribution systems. This overlap between human and NTM environments afforded new opportunities for human exposure, and for expression of their often neglected and underestimated pathogenic potential. Some risk factors predisposing to NTM disease have been identified and are mainly associated with immune fragilities of the human host. However, infections in apparently immunocompetent persons are also increasingly reported. The purpose of this review is to bring attention to this emerging health problem in Portugal and Brazil and to emphasize the urgent need for increased surveillance and more comprehensive epidemiological data in both countries, where such information is scarce and seriously thwarts the adoption of proper preventive strategies and therapeutic options.